Preface / Ts. Jamal Othman - Othman, Jamal (Unit Penerbitan JSKM, 2022)
The committee of SIG CS@e-Learning would like to express our sincere gratitude to Allah S.W.T for the fourth articles publication shared by lecturers from the Department of Computer & Mathematical Sciences, UiTM Penang Branch. Total of 10 articles have been submitted and all papers were accepted for publication. The articles submitted, have shown that the quality of contents and research framework discussed are potentially to be published in those journals indexed by SCOPUS, WOS or ERA. Although, the articles submitted within 6 to 8 pages, the authors are able to explain academically and professionally. The theme of fourth volume focusing on innovation of science and digital technology in e-Learning future trends. The integration of e-learning innovations is the current challenges for organisations in Higher Education in order to support learning, teaching, and administrative processes. The popularity of online courses has increased over the past decade, and the global online learning market is expected to reach $325 billion by 2025. New trends in e-learning will be covered under artificial intelligence (AI), micro credentials, big data, virtual and empowered reality, blended learning, cloud e-learning, gamification, mobile learning, Internet of things, and online video.